Exploring the effect of perceived overqualification on knowledge hiding: The role of psychological capital and person-organization fit - Zhu, Jing; Lin, Fangyu; Zhang, Ying; Wang, Shanshan; Tao, Wenxing; Zhang, Zhenyong (Frontiers in Psychology, 2022)
Individuals’ knowledge hiding behavior may lead to massive economic losses to organizations, and exploring the antecedents of it has crucial relevance for mitigating its negative influences. This research aims to investigate the impact of perceived overqualification on knowledge hiding by testing the mediating effect of psychological capital and the moderating effect of person-organization fit. Empirical analyses were conducted on 249 employee dataset using versions SPSS 26 and AMOS 26. Results illustrate an inverse correlation between perceived overqualification and knowledge hiding behavior which is partly mediated by psychological capital and moderated by person-organization fit, implying that good organizational atmosphere that builds up individual psychological capital with better person-organization fit will allow employees to work positively to reduce knowledge hiding behavior when perceived overqualified. This study complements a small quantity of discussions on the positive impact of perceived overqualification on knowledge management and fills omissions in previous studies on the negative effect of perceived overqualification on knowledge hiding behaviour in changing surroundings.